CRUELTY OF SLAVERY IN AMERICA AS SEEN IN HARRIET BEECHER STOWE’S UNCLE TOM’S CABIN - Pipin Apriola; Agustine Mamentu; Tirza Kumayas (KOMPETENSI, 2022)
The purpose of this research is to examine the cruelty of slavery in America as shown inHarriet Beecher Stowe's Uncle Tom's Cabin. It is done to show the many sorts ofenslavement cruelty present in the novel, as well as the causes of the brutality in thestory. The writers have decided to undertake this research using qualitative methods.The writers employ a socio-historical method to data analysis. In the discussion isdivided into several indicators, such as cruelty of slavery which is divided into slavetreat as thing or properties and object of physical violence. The other indicator is slavessuffer as the effect cruelty of slavery which divided into racism, discrimination, slaves’life is restricted and rebellion. Based on the results of the discussion, it can be concludedthat slavery has happened to black people who are very cruel in America and evenlegalized. South Americans treat black people as slaves inhumanely and treat them likeanimals.